What's in an accent? General spontaneous biases against nonnative accents: An investigation with conceptual and auditory IATs. (3rd November 2017) - Roessel, Janin; Schoel, Christiane; Stahlberg, Dagmar
Abstract: Nonnative accents are prevalent in our globalized world and constitute highly salient cues in social perception. Whereas previous literature has commonly assumed that they cue specific social group stereotypes, we propose that nonnative accents generally trigger spontaneous negatively biased associations (due to a general nonnative accent category and perceptual influences). Accordingly, Study 1 demonstrates negative biases with conceptual IATs, targeting the general concepts of accent versus native speech, on the dimensions affect, trust, and competence, but not on sociability. Study 2 attests to negative, largely enhanced biases on all dimensions with auditory IATs comprising matched native–nonnative speaker pairs for four accent types. Biases emerged irrespective of the accent types that differed in attractiveness, recognizability of origin, and origin‐linked national associations. Study 3 replicates general IAT biases with an affect IAT and a conventional evaluative IAT. These findings corroborate our hypotheses and assist in understanding general negativity toward nonnative accents.